Thursday

November 27, 2014

November 27, 2014

Posted by **sara** on Sunday, May 17, 2009 at 6:43am.

x^2-1/x-3 * 4x-12/x^2-x-2

- algebra -
**drwls**, Sunday, May 17, 2009 at 7:22amYou can factor out some terms.

(x^2-1)/(x-3) * (4x-12)

= [(x+1)(x-1)/(x-3)]*4(x-3)

= 4(x+1)(x-1)

The divisor (x^2 -x -2) can be rewritten

(x-2)(x+1), so the (x+1) terms can also be cancelled out. That leaves you with

4(x-1)/(x-2)

**Answer this Question**

**Related Questions**

algebra - Solve. x/9-1/7=26/63 STEP 1: The LCM is _________ To clear ...

Math(Please respond) - .50 - x / x = 3.20e-1 I need to solve for x. I was going...

Algebra - How do I solve for elimination method on this problem: 0.3x - 0.2y=4 ...

Intermediate Algebra Solve - Solve: -1/3 - 5/4t = 3/4 - 1/6t would I cross ...

Math Help Please... - x/3-2/3=1/x *Solve the rational below. I really need help...

please help math - x/3-2/3=1/x *Solve the rational below. I really need help. ...

Chemistry(Please check) - .50 - x / x = 3.20e-1 I need to solve for x. I was ...

algebra - Please help f(x) = 3x² + 2 x= 3 my question, do I start by solving x² ...

Algebra - multiply (n^3+8)(n-4) can you give me an example on how to solve this ...

Algebra - multiply (n^3+8)(n-4) can you give me an example on how to solve this ...